Synaptic proteomics decode novel molecular landscape in the brain - Ito, Yuki; Nagamoto, Sayaka; Takano, Tetsuya (Frontiers in Molecular Neuroscience, 2024)
Synapses play a pivotal role in forming neural circuits, with critical implications for brain functions such as learning, memory, and emotions. Several advances in synaptic research have demonstrated the diversity of synaptic structure and function, which can form thousands of connections depending on the neuronal cell types. Moreover, synapses not only interconnect neurons but also establish connections with glial cells such as astrocytes, which play a key role in the architecture and function of neuronal circuits in the brain. Emerging evidence suggests that dysfunction of synaptic proteins contributes to a variety of neurological and psychiatric disorders. Therefore, it is crucial to determine the molecular networks within synapses in various neuronal cell types to gain a deeper understanding of how the nervous system regulates brain function. Recent advances in synaptic proteome approaches, such as fluorescence-activated synaptosome sorting (FASS) and proximity labeling, have allowed for a detailed and spatial analysis of many cell-type-specific synaptic molecules in vivo. In this brief review, we highlight these novel spatial proteomic approaches and discuss the regulation of synaptic formation and function in the brain. This knowledge of molecular networks provides new insight into the understanding of many neurological and psychiatric disorders.